2014
DOI: 10.1016/j.str.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Loop 4 of the Proline Transporter PutP Controls the Periplasmic Entrance to Ligand Binding Sites

Abstract: The Na(+)/proline symporter (PutP), like several other Na(+)-coupled symporters, belongs to the so-called LeuT-fold structural family, which features ten core transmembrane domains (cTMs) connected by extra- and intracellular loops. The role of these loops has been discussed in context with the gating function in the alternating access model of secondary active transport processes. Here we report the complete spin-labeling site scan of extracellular loop 4 (eL4) in PutP that reveals the presence of two α-helic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 64 publications
(132 reference statements)
1
40
0
Order By: Relevance
“…Although we speculate, based on our results, that the role of the conserved Na2 site is to stabilize substrate binding without conformational selection, analysis of other Na + -coupled transporters is needed to test this conjecture. Kinetic and conformational investigations of putative LeuT-fold members, hSGLT and PutP, have begun to tease out such details (23,36,37). Such analysis will also test a similarly tantalizing notion that subclasses of ion-coupled LeuT-fold transporters, defined by their transport modes and/or type and number of symported ions, share commonalities in their structural mechanics of alternating access.…”
Section: Discussionmentioning
confidence: 99%
“…Although we speculate, based on our results, that the role of the conserved Na2 site is to stabilize substrate binding without conformational selection, analysis of other Na + -coupled transporters is needed to test this conjecture. Kinetic and conformational investigations of putative LeuT-fold members, hSGLT and PutP, have begun to tease out such details (23,36,37). Such analysis will also test a similarly tantalizing notion that subclasses of ion-coupled LeuT-fold transporters, defined by their transport modes and/or type and number of symported ions, share commonalities in their structural mechanics of alternating access.…”
Section: Discussionmentioning
confidence: 99%
“…The L406E mutation could possibly impair interactions to these domains and thereby hinder SERT from entering the inward-facing conformation. A recent study of the bacterial LeuT-fold transporter, PutP, has suggested that interactions between residues on TM1 and EL4 (equivalent to Trp 103 (TM1) and Phe 407 (EL4), respectively, in human SERT) are important for transporter function (35). Furthermore, mutation of Trp 33 in the bacterial SLC6 homologue MhsT (equivalent to Trp 103 in human SERT) reduced functional uptake activity, supposedly by enhancing the transition to the inward-facing conformation (41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on bacterial transporters have suggested that interactions between a hydrophobic residue on TM1 (equivalent to Trp 103 in human SERT) and a Phe residue on EL4 (equivalent to Phe 407 in human SERT) is important for the transition from outward-to inward-facing conformation (35,41). To test if the L406E-induced effects were caused by disruption of the proposed TM1-EL4 interaction, we substituted Trp-103 for Ala in the background of L406E in SERT.…”
Section: L406e Renders the Cytoplasmic Permeation Pathway Less Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the lipid dependency of the conformational-energy landscape has been evaluated [139]. The SLC6A family, which is better known as LeuT family, has been exemplified based on the Na + -coupled amino acid symporter LeuT [140,141]), the Na + /hydantoin symporter Mhp1 [142] and the Na + /proline symporter PutP [143][144][145][146]. All studies are in agreement with the suggested combination of the rocker-switch and gating-type mechanisms in order to achieve alternating access.…”
Section: Secondary Active Proteinsmentioning
confidence: 99%